Comparison of Static and Single-Axis Solar Tracking System Performance on 270 Wp Solar Panels - Rahmad Dwi Kurniawan; RD. Kusumanto; Johansyah Al Rasyid (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study investigates the performance comparison between a static solar panel and a single-axis solar tracking system controlled by a Real Time Clock (RTC), using a 270 Wp photovoltaic module. The system adjusts the panel’s orientation based on scheduled time intervals to follow the sun’s path from east to west. The experiment was conducted over two days under similar weather conditions, measuring voltage, current, and power output at hourly intervals. Results show that the RTC-based tracking system consistently provided more optimal power output throughout the day, especially during the early morning and late afternoon when fixed panels are less efficient. These findings demonstrate that time-based solar tracking can improve energy harvesting efficiency and offer a practical and cost-effective solution for small-scale renewable energy applications, particularly in tropical regions.